Experimental and numerical analysis on frost heave cracking of prestressed high-strength concrete (PHC) pipe piles in cold regions - Yin, Xiao; Zhang, Fa; Wu, Jianxin; Jia, Mutian; Lacidogna, Giuseppe; Xu, Jie (Frontiers in Materials, 2025)
With the depletion of global fossil energy and the rapid development of photovoltaic power, prestressed high-strength concrete (PHC) pipe piles are widely applied in photovoltaic projects due to their superior mechanical properties and ease of construction. However, PHC pipe piles in cold regions face severe challenges of vertical cracks, which reduce the bearing capacity of the piles and threaten the safe operation of photovoltaic equipment. Motivated by a field case study of extensive cracking at a large-scale photovoltaic site, this paper investigates the failure mechanism through a combination of laboratory experiments and finite element (FE) analysis. The results reveal that the freezing and expansion of a sufficient volume of accumulated internal water is the necessary and definitive condition for vertical cracking, while pre-existing defects act only as promoting factors. A critical water level threshold for cracking was identified, and a subsequent parametric analysis demonstrated that this threshold is highly sensitive to design parameters. Specifically, the critical water level increases significantly with greater wall thickness and higher concrete strength, but is largely unaffected by the level of axial prestress. The findings are corroborated by the field data, which shows a strong correlation between the highest rates of pile failure and water-rich environmental conditions. This study provides a quantitative framework for engineers to assess the risk of frost heave and offers a scientific basis for developing effective preventive measures to enhance the durability of photovoltaic infrastructure in cold regions.